White on blue: A study on underglaze-decorated ceramic tiles from 15th-16th-century Valencian and Sevillian productions. (April 2020) - Coentro, S.; Alves, L.C.; Coll Conesa, J.; Ferreira, T.; Mirão, J.; da Silva, R.C.; Trindade, R.; Muralha, V.S.F.
Graphical abstract: Highlights: Multi-analytical characterisation of a unique historical ceramic technology. Underglaze decoration using an opaque white tin-glaze over the pigment layer. New features to distinguish Hispano-Moresque ceramic production centres. Abstract: This study characterises and compares tin-opacified underglaze-decorated tiles from Valencian and Sevillian provenances. This technique, where the cobalt and manganese pigments are applied below an opaque white glaze, was used in the Iberian Peninsula between the 14th and early 16th centuries. The chemical and morphological characterisation of the glazes was performed by Optical Microscopy (OM), Scanning Electron Microscopy with Energy-Dispersive X-Ray Spectroscopy (SEM-EDS), µ-Raman Spectroscopy, and µ-Particle-Induced X-Ray Emission (µ-PIXE). Both the morphology of the glazes and their chemical composition allowed for the distinction between the two production centres. Sevillian glazes exhibit a thicker pigment layer, as well as higher SnO2 and lower K2 O contents than the Valencian ones. Furthermore, the SEM analysis of cobalt pigment particles identified an interior nucleus rich in Co, Fe and Ni, and an exterior layer rich in Si, Ca, Mg and Na, suggesting that the pigment was used mixed with clay or sand.